Bluetongue virus VP4 is an RNA-capping assembly line. - Sutton, G; Grimes, J; Stuart, D; Roy, P (2007)
Eukaryotic organisms cap the 5' ends of their messenger RNAs by a series of four chemical reactions. Some viruses achieve this using a single molecule; the crystal structure of such an enzyme from bluetongue virus reveals an elongated modular architecture that provides a scaffold for an assemblage of active sites, two contributed by a domain of novel structure.